2022
DOI: 10.1111/bph.15911
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine kinase inhibitor nilotinib targets the discoidin domain receptor DDR2 in calcific aortic valve stenosis

Abstract: Background and Purpose: Tyrosine kinase inhibitors (TKI) used to treat chronic myeloid leukaemia (CML) have been associated with cardiovascular side effects, including reports of calcific aortic valve stenosis. The aim of this study was to establish the effects of first and second generation TKIs in aortic valve stenosis and to determine the associated molecular mechanisms.Experimental Approach: Hyperlipidemic APOE*3Leiden.CETP transgenic mice were treated with nilotinib, imatinib or vehicle. Human valvular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This ultimately leads to a proarrhythmic effect of nilotinib [46]. Carracedo et al showed that nilotinib increased murine aortic valve thickness, promoted calcification and osteogenic activation, and decreased autophagy in human valvular interstitial cells suggesting that nilotinib may have additional cardiotoxicity in some patients [47]. A meta-analysis from 2022 concluded that nilotinib should not be recommended to patients with advanced age, previous cardiovascular disease, high-risk factors, or a previous cardiovascular adverse event, and that nilotinib should be completely avoided as a first-line drug because of its cardiotoxicity [48].…”
Section: Nilotinibmentioning
confidence: 99%
See 1 more Smart Citation
“…This ultimately leads to a proarrhythmic effect of nilotinib [46]. Carracedo et al showed that nilotinib increased murine aortic valve thickness, promoted calcification and osteogenic activation, and decreased autophagy in human valvular interstitial cells suggesting that nilotinib may have additional cardiotoxicity in some patients [47]. A meta-analysis from 2022 concluded that nilotinib should not be recommended to patients with advanced age, previous cardiovascular disease, high-risk factors, or a previous cardiovascular adverse event, and that nilotinib should be completely avoided as a first-line drug because of its cardiotoxicity [48].…”
Section: Nilotinibmentioning
confidence: 99%
“…In 2010, another second-generation TKI named dasatinib (trade name Sprycel), was approved by the FDA for use in patients who have resistance or intolerance to imatinib and newly diagnosed CML patients who are in chronic phase [57]. The thiazole-carboxamide structure of dasatinib is unique in that it binds to both the active and inactive conformations of BCR-ABL whereas imatinib and nilotinib only bind to the inactive form of BCR-ABL [47]. Various investigations have demonstrated that this dual-binding activity makes dasatinib more efficacious in resistant and intolerant patients [57].…”
Section: Dasatinibmentioning
confidence: 99%
“…264 However, nilotinib has been shown to block discoidin domain 2, increasing aortic calcification and coagulation. 265,266 Thus, nilotinib should not be used in ApoE-related neurodegeneration. Imatinib has a better profile since it reduces lesions in experimental models of multiple sclerosis.…”
Section: Nilotinib and Masitinibmentioning
confidence: 99%
“…Among mechanosensitive channels, TREK-1, Kir6.1, TRPV4, and TRPC6 are found in aortic VICs, with TRPV4 channel affecting the expression of collagen III in response to mechanical stretch 65 while inhibiting the DDR2, which directly senses collagen fibers, produces fibrosis and RunX2-mediated osteogenic calcification of the valve. 66 …”
Section: Impact Of Biomechanical and Ecm Alterations In Cavs Mechanismsmentioning
confidence: 99%